Perbedaan penemuan Foreign Object Debris (FOD) Sebelum dan Selama Haji Tahun 2022 untuk Menunjang Keamanan Penerbangan di Bandar Udara Internasional Adi Soemarmo Boyolali Jawa Tengah - Suci, Dinny Purnama; Kusuma, Nur Makkie Perdana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Every airport always has Foreign Object Debris (FOD), be it on the apron, runway or taxiway. Adi Soemarmo International Airport is one of the airports that serves regular flights and Hajj flights. Each flight takes off and lands on the runway and parks on the apron. Adi Soemarmo International Airport has routine daily work carried out by the engineering unit and supervised by the Apron Movement Control (AMC) unit, namely sweeping Foreign Object Debris (FOD). This study aims to determine the difference in Foreign Object Debris (FOD) in May (before Hajj) and in June (during Hajj). In addition, this study also aims to obtain the results of differences in the number and type in May-June. This study used a quantitative descriptive method with a documentation study data collection method and secondary data from the number of daily sweeps of Foreign Object Debris (FOD) in May-June 2022, namely before and during Hajj at Adi Soemarmo International Airport. The method used to analyze the data in this study was to use a two-sample t-test in pairs. The results of this study show that there are significant differences in the types of Foreign Object Debris (FOD) and show that there are no significant differences between Foreign Object Debris (FOD) in May and June 2022 with H0 not being accepted because there are no significant results from the two differences with a ratio of 1:1.015 and for the difference from May and June of 15. Keywords: Foreign Object Debris (FOD), Difference, Before and during Hajj.